Communication Strategy in Building Corporate Image (a Case Study on PT KAI Divre IV Tanjungkarang) - Ulfa, Wardah; Hernawan, Wawan; Poyo, M Denu (CONVERSE Journal Communication Science, 2025)
This study aims to analyze the communication strategies implemented by PT KAI Divre IV Tanjungkarang in building a positive corporate image. The research uses a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The findings show that PT KAI employs external strategies via Instagram @siger.railway, mass media, and safety campaigns, while internal strategies include officer training and inter-departmental coordination. The research is analyzed using Weber’s Social Action Theory and Blumer’s Symbolic Interactionism, revealing that the company’s communication acts are rational, symbolic, and consistent in building public trust.